The Weakness of Government in Its Relation to Economy and of the Economic Theory of the State - Wilkin, Jerzy (Journal of Public Governance, 2010)
The government (state) and the market are the two main mechanisms which regulate the economy and the society. However, the theory of the state (government) is a neglected part of contemporary economics. This situation has a negative impact on the state’s activity. In Poland, the public sector reforms are much less advanced than in the private, market-oriented sector. Globalization and European integration have contributed new aspects and arguments to the dispute about the role of the government, but contrary to earlier expectations, they have not undermined the importance of the state. Improvement of both the state’s activity and the quality of public governance are permanent challenges for scientists and for societies. As we can observe, the theory of the state has been a more difficult part of economics than the theory of the market.